Transdermal absorption enhancement of gel containing elastic niosomes loaded with gallic acid from Terminalia chebula galls - Aranya Manosroi (2018)
Objectives: To investigate transdermal absorption enhancement of gel containing elastic niosomes loaded with gallic acid in the semipurified fraction isolated from Terminalia chebula Retz. (Combretaceae) galls. Materials and methods: Nonelastic and elastic niosomes loaded with gallic acid in pure form or in the semipurified fraction were developed. Rat skin permeation by vertical Franz diffusion cells of gallic acid from various gel formulations containing elastic niosomes loaded with gallic acid or the semipurified fraction was performed. Results: Elastic and nonelastic niosomes loaded with gallic acid or the semipurified fraction exhibited the mixture of unilamellar and multilamellar structures with negative zeta potential values and in the size range of 200-400nm. Both loaded elastic and nonelastic niosomes showed good physical and chemical stability for 3 months. The percentages remaining of gallic acid in nonelastic were slightly higher than in elastic niosomes. Both elastic and nonelastic niosomes retarded rat skin permeation of the loaded pure gallic acid, while enhanced the loaded gallic acid in the semipurified fraction. However, elastic niosomes exhibited higher percentages of gallic acid through rat skin than the nonelastic niosomes. Discussion and conclusion: This study has demonstrated the potential of niosomes, especially elastic niosomes, for the enhancement of chemical stability and rat skin transdermal absorption of gallic acid in the semipurified fraction from T. chebula galls, which will be beneficial for topical antiaging application. © 2011 Informa Healthcare USA, Inc.